2021
DOI: 10.3390/infrastructures6110151
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pavement Subgrade by Adding Cement and Fly Ash to Natural Desert Sand

Abstract: Soil characteristics are paramount to design pavements and to assess the economic viability of a road. In the desert, such as that found in southern Libya, the very poor quality of soils leads to important pavement distress such as cracks, rutting, potholes, and lateral shear failure on the edges. To improve the strength of desert sand, an innovative approach is proposed, consisting of adding manufactured sand, ordinary Portland cement (OPC), and fly ash (FA) as a binder. OPC and FA improve the characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The mechanical and chemical stabilization alteration of one or more soil properties has been termed as soil stabilization [ 21 , 22 ]. Most researchers studied to improve the engineering properties by increasing the compressive strength of the soil [ 6 , 8 , 12 , 16 , 17 , 23 ] according to the ASTM D 4609 standard [ 24 ] (>0.8 Mpa). Soil stabilization can be described as a collective term for any physical, chemical, or combination of those approaches used to enhance certain features of natural soil in order for it to meet the engineering requirements [ 3 , 4 , 9 , 10 , 11 , 15 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and chemical stabilization alteration of one or more soil properties has been termed as soil stabilization [ 21 , 22 ]. Most researchers studied to improve the engineering properties by increasing the compressive strength of the soil [ 6 , 8 , 12 , 16 , 17 , 23 ] according to the ASTM D 4609 standard [ 24 ] (>0.8 Mpa). Soil stabilization can be described as a collective term for any physical, chemical, or combination of those approaches used to enhance certain features of natural soil in order for it to meet the engineering requirements [ 3 , 4 , 9 , 10 , 11 , 15 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the soft subgrade soil (Itapeti) did not meet the design requirements individually and faced the possibility of ineffective compaction using a RMFRM, the material was stabilised with RFBW and 3% cement. Previous studies have highlighted the positive potential of a low percentage of cement to improve the hydro-mechanical properties, compaction, and stabilisation of pavement materials [50][51][52][53][54]. On the other hand, the stiff subgrade soil SPAB, while suitable for subgrade applications, did not require stabilization.…”
Section: Physical-chemical Characterisation and Dosagementioning
confidence: 99%
“…Previous studies have shown that the addition of cement, lime, and other cementing materials to aeolian sand can improve the compactness of aeolian sand and reduce its porosity, thus improving its compressive, shear, and tensile strength [ 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. At present, aeolian sand has been widely used in the preparation of mortar, concrete, and roadbed filler [ 18 ].…”
Section: Introductionmentioning
confidence: 99%